Causal roles of mitochondrial dynamics in longevity and healthy aging. (31st October 2019) - Sharma, Arpit; Smith, Hannah J; Yao, Pallas; Mair, William B
Abstract: Mitochondria are organized in the cell in the form of a dynamic, interconnected network. Mitochondrial dynamics, regulated by mitochondrial fission, fusion, and trafficking, ensure restructuring of this complex reticulum in response to nutrient availability, molecular signals, and cellular stress. Aberrant mitochondrial structures have long been observed in aging and age‐related diseases indicating that mitochondrial dynamics are compromised as cells age. However, the specific mechanisms by which aging affects mitochondrial dynamics and whether these changes are causally or casually associated with cellular and organismal aging is not clear. Here, we review recent studies that show specifically how mitochondrial fission, fusion, and trafficking are altered with age. We discuss factors that change with age to directly or indirectly influence mitochondrial dynamics while examining causal roles for altered mitochondrial dynamics in healthy aging and underlying functional outputs that might affect longevity. Lastly, we propose that altered mitochondrial dynamics might not just be a passive consequence of aging but might constitute an adaptive mechanism to mitigate age‐dependent cellular impairments and might be targeted to increase longevity and promote healthy aging. Abstract : Mitochondria form a dynamic, interconnected network that is shaped by fusion, fission and trafficking. This review discusses how aging affects mitochondrial dynamics and how such alterations in turn might help the organism to cope with age‐dependent cellular impairments.